Acute chest pain in contingency operations at a Role 1 facility. Issue 3 (11th August 2015) - Barker, Steven; White, S; Bailey, K; Rees, P
Abstract : Acute chest pain is a common medical presenting complaint which can be difficult to diagnose and treat outside of a fully equipped emergency department. In future contingency operations the number of personnel deployed is likely be smaller, with the medical cover appropriate for the population at risk, such that the deployed medical facilities will be smaller than the Role 3 unit with which we have become familiar over the last 10 years of operations in Afghanistan. Physician involvement in these smaller medical facilities is crucial to maintain clinical effect when dealing with patients presenting with disease and non-battle injury, which can often make up the majority of deployed healthcare work. Patients presenting with chest pain require rapid assessment and stabilisation prior to medical evacuation to a suitable definitive care unit. This article focuses on emergency acute chest pain presentations, non-cardiac causes of chest pain, risk reduction and how contingency will affect patient care.